Perancangan Interior Pusat Perbelanjaan Khusus Wanita di Surabaya dengan Konsep Elegant Beauty - Poppy F Nilasari, Metta Dewi Martino Dwi Nugroho (Intra, 2014)
This work design is motivated by womens need for shopping specially for a big city like Surabaya. This need would need to be facilitated. A Shopping center which have few retails and a place to relax is demand by women. Therefore, designing shopping center interior for women in Surabaya was made.                The design theme is "elegant beauty" which is compactible with women character, target design is a women teenage and women young adult. This shopping center for women design project expected to become an example for other shopping center for specializing shopping center for women.